What is considered important for life balance?: Similarities and differences among some working adults - Wagman, P.; Hakansson, C.; Jacobsson, C.; Falkmer, Torbjorn; Bjorklund, A. (Informa Healthcare, 2012)
Life balance seems subjective, health related, and multidimensional. However, the concept is complex. Exploring what people themselves consider more or less important for their life balance and whether this differs between people would develop new knowledge. Q methodology was chosen for the present study, in which 32 working men and women without recent long-term sick leave participated. They sorted 42 statements regarding life balance according to their importance for each participant’s life balance. The analysis resulted in four different viewpoints concerning life balance. All four viewpoints considered good relationships with those closest to them, as well as knowing that these people were doing well, as important. Each viewpoint also showed a unique orientation towards what was considered important for life balance: occupational balance (viewpoint 1), self-actualization (viewpoint 2), self-awareness (viewpoint 3), and reciprocal relationships (viewpoint 4). The results showed support for life balance as being a subjective, multidimensional, and health-related phenomenon. The results demonstrated the importance of relationships for life balance and heterogeneity in what people considered important for their own life balance.